Biofilm developed on plant substrates enhances growth and survival of post larvae of Macrobrachium rosenbergii - Madathumpady Thomas, Shilta; Lalramchhani, Christina; Lalrinsanga, P. L.; Pillai, Bindu (Fishery Technology, 2020)
A five-week laboratory experiment was conductedto evaluate the efficacy of plant-based substrates forbiofilm production and their effect on water qualityas well as growth and survival of freshwater prawnMacrobrachium rosenbergii (De Man, 1879) postlarvae.The experiment consisted of three treatmentswith a control, each with three replicates followinga completely randomized design. The substratesevaluated were dried sugarcane bagasse (T1), paddystraw (T2) and Eichhornia (T3). Tanks withoutsubstrates acted as control. Seven days after theintroduction of substrates at the rate of 300 g /tank,post-larvae were stocked at 40 nos/m2. The meaninitial length and weight of the post-larvae was10.3 mm and 0.008 g, respectively. The post-larvaewere fed with commercial pellet feed (30% protein)at 20% of initial biomass. Results revealedsignificantly higher (p